2022
DOI: 10.1016/j.deveng.2022.100094
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed activated charcoal inlet filters for oxygen concentrators: A circular economy approach

Abstract: As of May 2021, the current COVID-19 pandemic is still plaguing the world, challenging all the countries and their health systems, globally. In this context, conditions typical of low-resource settings surfaced also in high-resource ones (e.g., the lack of essential medical equipment, of resources etc.), while exacerbating in the already resource-scarce settings, because of COVID-19. This is the case of oxygen concentrators that are one of the first-line medical devices for treating COVID-19 patients. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…To better understand the pressurization and depressurization processes taking place inside the microporous region of nanosized zeolites, a simulation of the pressure and vacuum swing adsorption units was devised ( 92 ). Besides this, several investigators have also reported the surface modification of such nanozeolites by other metallic particles to make the process more efficient ( 1 , 97–99 ).…”
Section: Role Of Nanotechnology In Oxygen Concentratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the pressurization and depressurization processes taking place inside the microporous region of nanosized zeolites, a simulation of the pressure and vacuum swing adsorption units was devised ( 92 ). Besides this, several investigators have also reported the surface modification of such nanozeolites by other metallic particles to make the process more efficient ( 1 , 97–99 ).…”
Section: Role Of Nanotechnology In Oxygen Concentratorsmentioning
confidence: 99%
“…Oxygen is the basic requirement for both a healthy and a diseased individual. There are certain medical diseases, especially cardiovascular respiratory disorders, where there is a requirement for pure or concentrated oxygen by the patient ( 1 , 2 ). This pure or concentrated oxygen is indeed known as medical oxygen, and in the absence of it, a patient may experience hypoxemia [low levels of oxygenated blood ( 3 )].…”
Section: Introductionmentioning
confidence: 99%
“…Pending further validation, this system could be suitable for incorporation into a diagnostic tool such as an application for use on a mobile phone. Similarly, Ellis et al [64] presented the redesign of the inlet filter of an oxygen concentrator. The redesign is based on a reverse engineering approach, which makes use of activated charcoal coupled with 3D-printing methods, to accommodate environmental conditions that present in many African countries.…”
Section: Table II Frequency Distribution Of Technology Usedmentioning
confidence: 99%
“…Over the past century, healthcare provision in low-resource settings (LRS) in sub-Saharan Africa (SSA) has been hampered by underfunded healthcare infrastructures ( 1 3 ). This results in a lack of medical devices crucial to provide healthcare for all ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, this high volume of donations should drastically improve the availability of functioning medical devices in LRS ( 3 ). Nevertheless, these initiatives have been estimated to be unsuitable and unsustainable ( 3 ). Estimates suggest that about 40% of medical devices donated are non-functional, thus leaving healthcare facilities in LRS with the issue of medical device unavailability and excessive waste streams of defunct devices ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%